SiC honeycomb reinforced Al matrix composite with improved tribological performance. Issue 16 (15th August 2021) - Zhang, Zhejian; Wei, Zhilei; Li, Zhiyuan; Hou, Baoqiang; Xue, Rong; Xia, Hongyan; Shi, Zhongqi
Abstract: SiC honeycomb ceramic reinforced Al (SiCH /Al) composite with anisotropic microstructure was fabricated by spontaneous infiltration method, and the effect of SiC honeycomb reinforcement on the tribological performance of SiCH /Al composite in axial and radial directions was investigated. The SiC particle reinforced Al (SiCP /Al) composite with the same SiC content was prepared as a counterpart to reveal the effect of SiC reinforcement architecture on the tribological performance of the Al-matrix composites. Compared with the SiCH /Al composite in radial direction and the SiCP /Al composite, the SiCH /Al composite in axial direction shows the highest thermal conductivity of 140.96 W m −1  K −1 and hardness of 97.14 H V, which hinder the formation of oxidative wear and eroding of counter ball. Additionally, a mechanical mixed layer can be formed on the worn surface of SiCH /Al composite in axial direction during the friction process. As a consequence, the SiCH /Al composite in axial direction exhibits the optimal tribological performance with the lowest averaged friction coefficient (0.53) and wear rate (0.98 mm 3  N −1  m −1 ). The results indicate that the SiC honeycomb reinforcement is a promising candidate to improve the tribological performance of metal-matrix composites, especially in their axial direction.